AN ANALYSIS THE USE OF VISUAL MEDIA IN TEACHING ENGLISH TO YOUNG LEARNERS - Sofian, Riska Febriany; Anggraeni, Anita (IKIP Siliwangi, 2021)
This research aims to describe the teacherâ€™s preparation and explain how the teacher utilized the media in teaching English in one of the elementary schools in Cimahi. This method used a descriptive qualitative. This research was conducted with two instruments. There is observation in the classroom and an interview with the teacher. The research subject was VIB grade students in one school in Cimahi. The result of this research that the teacher did three kinds of preparation, prepares a projector, understands the material for delivery to students and prepares the PowerPoint that uses in the classroom. In utilizing the media, the teacher uses a projector and PowerPoint as a media in teaching English.Â Keywords:Â Visual Media, PowerPoint, Young Learners